Estudio comparativo de rendimiento de ocho genotipos de Tabaco Negro (Nicotiana tahacum) bajo condiciones de Riego en el Bajo Mayo San Martin - Pérez Vargas, Francisco Alcides (1998)
This thesis was conducted at the Oasis-Morales, Cumbaza right bank of the river in the Lower Mayo, province and department of San Martin (Peru) sector. Geographically characterized by having the following coordinates: Latitude South with 6, January 18 and 73 ° 33 11 W and 323 meters above sea level. In order to compare the performance of eight genotypes of snuff Black (Nicotiana tabacum) under irrigation, varieties and hybrids used were: Brazil thin Mata, Gualaceo Ecuador, Habano Nicaragua, Pennland, Maryland, Tarapoto (Witness) and hybrids HNX (l4Bx513) xhj, ms. 215 x blc8,3x, .For the implementation of statistical design work complentamente Block used the Randonizado {B. E. R.) with eight treatments and three repetitions; The results were analyzed by analysis of variance and multiple test of Duncan. Based on production costs and economic analysis of profitability determin6 the T6, (variety Pennland), T7 treatments (Variety Maryland) achieved higher yields whose weights are 22, 40 and 761. 21, 675. 79 Kg / Ha and being lower yielding T1 (Brazil kills finish with 812.28 weighing 7 Kg / Ha.